Bacterial vaginosis—A brief synopsis of the literature. (February 2020) - Coudray, Makella S.; Madhivanan, Purnima
Abstract: Bacterial vaginosis (BV) affects women of reproductive age and can either be symptomatic or asymptomatic. Approximately 50 % of women are symptomatic and experience vaginal malodor, discharge, itching and increased vaginal pH. BV can increase the risk of contracting many sexually transmitted infections (STIs) such as human immunodeficiency virus (HIV), Neisseria gonorrhea (NG), Chlamydia trachomatis (CT), Trichomonas vaginalis (TV) and herpes simplex virus-2 (HSV-2). Though effective treatment options do exist, metronidazole or clindamycin, these methods have proven not to be effective long term. The purpose of this review is to summarize current literature on the epidemiology of BV and highlight areas of deficiency in current clinical practice with respect to BV. BV recurrence rates are high, approximately 80 % three months after effective treatment. Furthermore, in some instances treatment is ineffective and BV persists. Literature also documents the relationship between BV and human papillomavirus (HPV). HPV is the most common sexually transmitted infection among young adult women while BV is the most common cause of vaginal symptoms among women of reproductive age. BV is associated with high levels of anaerobic organisms which can damage the vaginal epithelium and increase the risk of HPV infection. Recent research also highlights the role of the vaginal microbiome in BV. The results of this review warrant further exploration into the etiology of BV as well as exploration of more long-term effective treatment and the investigation of prognostic indicators. Additionally, the need for a standard definition of recurrent and persistent BV is recognized.